Novel Insights Into Cellular Changes in HPV8-E7 Positive Keratinocytes: A Transcriptomic and Proteomic Analysis - Kirschberg, Matthias; Syed, Adnan Shahzad; Dönmez, Hanife Güler; Heuser, Sandra; Wilbrand-Hennes, Astrid; Alonso, Angel; Hufbauer, Martin; Akgül, Baki (Frontiers in Microbiology, 2021)
Human papillomavirus type 8 (HPV8) is associated with the development of non-melanoma skin cancer. In the past we already delved into the mechanisms involved in keratinocyte invasion, showing that the viral E7 oncoprotein is a key player that drives invasion of basal keratinocytes controlled by the extracellular protein fibronectin. To unravel further downstream effects in E7 expressing keratinocytes we now aimed at characterizing gene and protein/phosphoprotein alterations to narrow down on key cellular targets of HPV8-E7. We now show that gene expression of GADD34 and GDF15 are strongly activated in the presence of E7 in primary human keratinocytes. Further analyses of fibronectin-associated factors led to the identification of the Src kinase family members Fyn and Lyn being aberrantly activated in the presence of HPV8-E7. Phospho-proteomics further revealed that E7 not only targets cell polarity and cytoskeletal organization, but also deregulates the phosphorylation status of nuclear proteins involved in DNA damage repair and replication. Many of these differentially phosphorylated proteins turned out to be targets of Fyn and Lyn. Taken together, by using unbiased experimental approaches we have now arrived at a deeper understanding on how fibronectin may affect the signaling cascades in HPV8 positive keratinocytes, which may be key for skin tumorigenesis and that may also aid in the development of novel therapeutic approaches for betaHPV-mediated cancers.